Autorzy:Wojciech Babiański, Lech Chańko, Joanna Czarnowska, Grzegorz Janocha
Wydawnictwo:Nowa Era
Rok wydania:2016
Wyznacz wielomiany w(x)=2f(x)-3g(x) 4.53 gwiazdek na podstawie 15 opinii

`a)` 

`w(x)=2(x^5+1/2x^2+3)-3(-2x^4+x^2/3+2)=` 

`\ \ \ \ \ \ \ =2x^5+x^2+6+6x^4-x^2-6=` 

`\ \ \ \ \ \ \ =2x^5+6x^4`  

`st(w)=5` 

`su m a_w=2+6=8`  

 

 

 

`u(x)=1/2(-2x^4+x^2/3+2)-1/3(x^5+1/2x^2+3)=` 

`\ \ \ \ \ \ \ =-x^4+x^2/6+1-1/3x^5-1/6x^2-1=` 

`\ \ \ \ \ \ \ =-1/3x^5-x^4`  

`st(u)=5` 

`su ma_u=-1/3-1=-4/3` 

 

 

 

`b)` 

`w(x)=2(3x^5+6x^3-9x)-3(2x^5+4x^3-4x^2)=` 

`\ \ \ \ \ \ \ =6x^5+12x^3-18x-6x^5-12x^3+12x^2=` 

`\ \ \ \ \ \ \ =12x^2-18x` 

`st(w)=2` 

`su m a_w=12-18=-6` 

 

 

 

`u(x)=1/2(2x^5+4x^3-4x^2)-1/3(3x^5+6x^3-9x)=` 

`\ \ \ \ \ \ \ =x^5+2x^3-2x^2-x^5-2x^3+3x=` 

`\ \ \ =-2x^2+3x` 

`st(u)=2` 

`su ma_u=-2+3=1`